Exploration of the Need for Posbindu PTM Health Volunteers During the Covid-19 Pandemic - Binoriang, Dinasti Pudang; Rohmah, Nur Saily; Setyaningrum, Niken; Lestari, Sri (Journal of Language and Health, 2024)
The covid-19 pandemic has had a tremendous impact on every human being. All activities that cause crowds are not allowed to stop the spread of the covid-19 virus, including routine PTM Posbindu activities. The role of healthy volunteers is hampered and has an impact on its implementation. In carrying out their duties during a pandemic, health volunteers require special needs to ensure the success of PTM Posbindu activities. Explore the needs of PTM Posbindu health volunteers during the covid-19 pandemic. This research was qualitative research with a descriptive method, conducted by FGD and interviews and carried out on 7 informants, in the working area of ​​the Jetis Health Center Yogyakarta. Interviews were conducted with 1 informant from the Jetis Public Health Center Yogyakarta. In analyzing the data, this research uses open code 4.03 software. This shows that PTM Posbindu health volunteer needs in the form of the need for inspection tools, funding needs, skill training needs for health volunteers, and the need for health care tools to support. The pandemic condition has an impact on the termination of the implementation of PTM Posbindu activities.